The Urgency of Intelligent Talent Management and a Motivational Culture as Drivers of Improving SME Performance - Helman Suprapto; Sayyidi Sayyidi; Hajjatul Mabbruroh; Abd Salim (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This research falls within the area of Human Resource Management (HRM), specifically related to talent development and the formation of a work culture that supports business performance. In the context of SMEs in Madura, the urgency of intelligent talent management and a motivational culture is crucial given the limited resources and high demands for competitiveness in the digital economy era. This study aims to analyze the influence of intelligent talent management and a motivational culture on improving SME performance, as well as to identify the strategic contribution of both factors within the framework of strengthening SME human resource capacity. The research method used is a quantitative survey approach, involving 120 SME managers spread across four districts on Madura Island. The data collection instrument was a questionnaire with a Likert scale and was analyzed using multiple linear regression techniques. The results show that intelligent talent management has a positive and significant effect on SME performance, while a motivational culture acts as a reinforcement that can create a conducive work environment for increased productivity. Both variables make a real contribution to building value- and competency-based HR excellence. This study emphasizes the importance of an adaptive, strategic HRM approach based on local potential to improve the sustainability of small and medium enterprises. These findings provide policy implications for local governments and stakeholders in formulating SME development programs based on superior and competitive human resource management.